Santri Multi Etni Di Pondok Pesantren Raudlatul Ulum 1: (Studi Analisis Pendidikan Multi Etnis dengan Pendekatan Tafsir) - Busthomi, Yazidul (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
Raudlatul Ulum 1 Islamic Boarding School is an Islamic educational institution that functions as one of the fortresses of defense of Muslims, a center for preaching and a center for the development of Muslim society in Indonesia. The term Islamic boarding school was first known in Java, in Aceh it is known as Rangkah and Dayah, in West Sumatra it is known as Surau. Where the curriculum is always changing, improving and updating. In Indonesia, it has been recorded in the history of education that it has experienced several curriculum changes along with changes and demands of community needs. Management in the development of local culture at Raudlatul Ulum 1 Islamic Boarding School is carried out in the following stages, namely: 1. Planning stage, planning carried out for the development of local culture is by setting goals and analyzing regional potential so that programs can be determined to be implemented. 2. Organizing stage, organizing includes the selection of human resources and facilities needed to help the program that has been set run according to its goals. 3. Implementation stage, namely the form of implementation of the determination of goals and programs.